2018
DOI: 10.2174/1874331501812010123
|View full text |Cite
|
Sign up to set email alerts
|

Response of Seeds Quality of Sunflower to Inoculation with Single and Mixed Species of Indigenous Arbuscular Mycorrhizal Fungi

Abstract: Background: The sunflower seeds which are popular in Syria and Mediterranean countries as a roasted or salted snack, supply a large number of nutritious components including protein and minerals. A pot experiment was conducted to determine the impact of indigenous Arbuscular Mycorrhizal Fungi (AMF) on phosphorus (P), nitrogen (N), and protein content in seeds of confection-type hybrid sunflower (Helianthus annuus L.). The indigenous AMF including Glomus intraradices, Glomus mosseae, and Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Seed coating with AMF produced significantly taller plants (245.75 cm) and increased head diameter (29.48 cm) than those of the soil spraying (202.50; 26.98 cm) and noninoculated treatments (189.75 cm; 23.70 cm). Similarly, other studies revealed positive effects of AMF on plant height and head diameter (Soleimanzadeh, 2010;Kavitha and Nelson, 2014;Ibrahim, 2018;Kalaiyerasan et al, 2019).…”
Section: Yield Componentsmentioning
confidence: 59%
See 1 more Smart Citation
“…Seed coating with AMF produced significantly taller plants (245.75 cm) and increased head diameter (29.48 cm) than those of the soil spraying (202.50; 26.98 cm) and noninoculated treatments (189.75 cm; 23.70 cm). Similarly, other studies revealed positive effects of AMF on plant height and head diameter (Soleimanzadeh, 2010;Kavitha and Nelson, 2014;Ibrahim, 2018;Kalaiyerasan et al, 2019).…”
Section: Yield Componentsmentioning
confidence: 59%
“…(Bago et al, 2000;Govindarajulu et al, 2005;Jiang et al, 2017;Smith and Read, 2008). It was revealed that AMF is the most common type of useful microbial community in the soil (Heidari and Karami, 2014;Ibrahim, 2018). Mycorrhizal fungi induce plant growth through increasing the availability of mineral nutrients such as P, Zn and Cu (Phiri et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The dissimilarity of the colonizing effectiveness of the inoculums may be due to different species of fungi present in each of them, as [21] observed when using consortium inoculums of several Glomeromycota species. The different ability of fungi to take nutrients in the substrate, the interaction of fungi with biochar, the distinct amount of mycelium produced by the fungi of each inoculum reflected in unequal efficiency of taking P [22], along with the dissimilar affinity shown by Glomeromycota species in each inoculum with tomato plants [23], might have influenced the responses observed in our experiment. Chlorophyll content.…”
Section: Resultsmentioning
confidence: 93%
“…Experimental studies have focused on understanding the link between diversity and productivity in multistressed environments, where the presence of taxonomically distant AM fungal species can act as insurance to support plant growth despite challenging abiotic conditions (Yang et al, 2016;Thonar et al, 2014;Crossay et al, 2019;Gosling et al, 2016;Maherali and Klironomos, 2007). Few studies, however, have looked at how functional complementarity in the fungal community may affect nutrient exchange processes, even in the absence of stress factors (Mensah et al, 2015;Ibrahim, 2018;Jansa et al, 2005). AM fungi can differ in their ability to provide phosphorus to the plant (Drew et al, 2003;Giovannini et al, 2020), or in their access to host carbon (Zhu and Miller, 2003), and these differences should by themselves result into differences in the plant growth dynamics (Afkhami et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…AM fungi can differ in their ability to provide phosphorus to the plant (Drew et al, 2003;Giovannini et al, 2020), or in their access to host carbon (Zhu and Miller, 2003), and these differences should by themselves result into differences in the plant growth dynamics (Afkhami et al, 2014). While some studies have investigated how plant productivity is affected by fungi to plant supply (i.e., phosphorus transfer), (Jansa et al, 2005;Mensah et al, 2015;Ibrahim, 2018;Martignoni et al, 2020a), changes in productivity due to carbon transfer (i.e., plant to fungi supply) have remained unexplored.…”
Section: Introductionmentioning
confidence: 99%